Undergraduate Management Accounting Research in University of Tanjungpura: Past, Present and Future - Brata, Handi (Fakultas Ekonomi dan Bisnis, UNTAN, 2012)
This paper provides a review of 168 undergraduate theses submitted between the year 2002 and 2011 in management accounting topics. During this time, there is a changing interest of students in accounting research, especially in topic selection. To review the development of management accounting research in undergraduate level, this paper is structured according to the topics, theories and research methods used. The purposes of this review are to determine the main interest and map the past and current achievement of such research area in University of Tanjungpura. Based on the current trend and international hot debatable topics, the last section of this paper also gives a recommendation about the possible interesting topics for future research.